2013
DOI: 10.1186/1742-4755-10-7
|View full text |Cite
|
Sign up to set email alerts
|

Current methods and attitudes of women towards contraception in Europe and America

Abstract: BackgroundThe choice of available contraceptive methods has increased in recent years; however, recent data on women’s awareness of methods and reasons for their method choice, or reasons for changing methods, is limited. The aim of this study was to examine the use and awareness of contraceptive methods in the USA, UK, Germany, Italy and Spain.MethodsQuantitative survey of heterosexual women aged 25–44 years (n=2544), with no known infertility. Questions related to knowledge and use of contraceptive methods, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
64
1
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 18 publications
8
64
1
11
Order By: Relevance
“…8 Its usage varied from 35% in Spain to 63% in Germany. 8 Most common method used in our study group was condom (20%) followed by tubectomy 12.5%, CuT 7.5%, O.C. Pills 1.5%, Injectable contraceptive and safe period 0.5% each.…”
Section: Discussionmentioning
confidence: 99%
“…8 Its usage varied from 35% in Spain to 63% in Germany. 8 Most common method used in our study group was condom (20%) followed by tubectomy 12.5%, CuT 7.5%, O.C. Pills 1.5%, Injectable contraceptive and safe period 0.5% each.…”
Section: Discussionmentioning
confidence: 99%
“…Although abortion laws are relatively more lenient in the U.S. relative to Germany, abortion is legal in both countries; therefore, a comparable situation persists (Levine, 2004;Cygan-Rehm and Riphahn, 2014). All contraceptives are generally available for purchase in Germany and the U.S. and knowledge about contraception and awareness of different forms of contraception is almost complete in both countries (Johnson and Pion, 2013).…”
Section: Comparison To Us Resultsmentioning
confidence: 99%
“…The purpose of Family Planning Program is to actualize the harmony and balance of population policy in order to encourage the implementation of national and regional development pertaining to the population, foster partnerships, the increased prosperity, independence and resilience family. 7 The result of study which was conducted in five countries by Johnson et al, 8 reported that the greatest awareness of contraceptive use today is for contraceptive pills, with varying awareness, but awareness for the use of non-hormonal contraceptive method is still low. Study by Bailey et al, 3 in the United States demonstrates that the use of contraceptives before the age of 21 years in women workers can make the acceleration in the investment of the labor market women, where women workers have greater opportunities to work full time which means increasing work productivity.…”
Section: Discussionmentioning
confidence: 99%